An Isolable 2, 5‐Disila‐3, 4‐Diphosphapyrrole and a Conjugated Si=P−Si=P−Si=N Chain Through Degradation of White Phosphorus with a N, N‐Bis(Silylenyl)Aniline. Issue 37 (8th August 2022) - Xiong, Yun; Dong, Shicheng; Yao, Shenglai; Dai, Chenshu; Zhu, Jun; Kemper, Sebastian; Driess, Matthias
Abstract: White phosphorus (P4 ) undergoes degradation to P2 moieties if exposed to the new N, N ‐bis(silylenyl)aniline PhNSi 2 1 (Si =Si[N( t Bu)]2 CPh), furnishing the first isolable 2, 5‐disila‐3, 4‐diphosphapyrrole 2 and the two novel functionalized Si=P doubly bonded compounds 3 and 4 . The pathways for the transformation of the non‐aromatic 2, 5‐disila‐3, 4‐diphosphapyrrole PhNSi 2 P2 2 into 3 and 4 could be uncovered. It became evident that 2 reacts readily with both reactants P4 and 1 to afford either the polycyclic Si=P‐containing product [PhNSi 2 P2 ]2 P2 3 or the unprecedented conjugated Si =P−Si =P−Si =NPh chain‐containing compound 4, depending on the employed molar ratio of 1 and P4 as well as the reaction conditions. Compounds 3 and 4 can be converted into each other by reactions with 1 and P4, respectively. All new compounds 1 –4 were unequivocally characterized including by single‐crystal X‐ray diffraction analysis. In addition, the electronic structures of 2 –4 were established by Density Functional Theory (DFT) calculations. Abstract : A novel geminal N, N ‐bis(silylenyl)aniline 1 degrades white phosphorus (P4 ) furnishing the first isolable 2, 5‐disila‐3, 4‐ diphosphapyrrole 2 . The latter further reacts readily with P4 and 1 to afford the polycyclic Si=P‐containing species 3 or the unprecedented conjugated Si=P−Si=P−Si=NPh chain‐containing compound 4 depending on the molar ratio of the reactants. Moreover, the products 3 and 4 can be converted into each other when treated with 1 and P4, respectively.